Community food environment measures in the Alabama Black Belt: Implications for cancer risk reduction - Gyawu, Rebecca (Prev Med Rep, 2015)
In-store measures were utilized to evaluate the availability of healthy food choices and nutrition/health promotion messages for cancer risk reduction in the selected Alabama Black Belt counties/cities. Sixty one retail food outlets (RFOs) were audited in 12 Alabama Black Belt cities. Store types included convenience stores (49.2%), restaurants (19.7%), fast food restaurants (16.4%), small supermarkets (8.2%), and large supermarket and farmers' markets (3.3 %), respectively. Although there were low numbers of farmers' markets/street stands and large supermarkets, these had significantly (p < 0.0001) higher health scores than the other store types. A few health promotion messages were highly visible or obscurely positioned in some RFOs. The Alabama Black Belt food environment had limited opportunities for healthy food choices.